2010
DOI: 10.1093/annonc/mdp518
|View full text |Cite
|
Sign up to set email alerts
|

Absence of transforming growth factor-β type II receptor is associated with poorer prognosis in HER2-negative breast tumours

Abstract: To the best of our knowledge, this is the first report indicating the relevance of HER2 status in discriminating TGF-betaRII as a prognostic marker for DFS and OS in human BC. These data indicate that TGF-betaRII protein analysis in tumour cells could be introduced in clinical practice as additional prognostic biomarker in HER2-negative BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…HER2 expression was considered as positive (score 3+) and negative (score 0-1+). Samples with a score of 2+ were excluded from the analysis (15). This study was approved by the Academic Advisory Board of Soochow University.…”
Section: Study Participantsmentioning
confidence: 99%
“…HER2 expression was considered as positive (score 3+) and negative (score 0-1+). Samples with a score of 2+ were excluded from the analysis (15). This study was approved by the Academic Advisory Board of Soochow University.…”
Section: Study Participantsmentioning
confidence: 99%
“…It binds with a high affinity to TGF-β type II receptor (TGF-β-RII), which transactivates TGF-β type I receptor to initiate an intracellular signaling cascade by bringing about phosphorylation of 2 receptorregulated Smads (Smad2 and 3), recruiting the common-partner Smad (Smad4) to form the Smad4-Smad2/3 complexes, and translocating to the nucleus as the transcription factor to regulate expression of target genes (4). Thus far, the clinical prognostic role of TGF-β pathway components in human breast cancer remains elusive, which may be due to the complexity introduced by a variety of other molecules and systemic factors, such as estrogen receptor α and human epidermal growth factor receptor 2 status, common-partner and inhibitory Smads, early-age onset, and menopausal status (1,(5)(6)(7)(8)(9)(10)(11). While several studies have been published on the prognostic role of pathway components such as TGF-β receptors, Smad2/3, and other regulatory molecules, their results conflict with respect to the association of cancer survival with expression of TGF-β-RII (7-9) and pSmad2/3 and pSmad4 in breast cancer cells (11,12).…”
mentioning
confidence: 99%
“…Whereas, it was shown in this study that higher TGFBR2 mRNA expression was associated with better relapse-free survival for patients with negative lymph node status ( Figure 5-4 B). This finding was more in agreement with Paiva et al's study which showed that TβRII down-expression was significantly associated with breast cancer and the absence of TβRII was an adverse prognostic factor [163]. Patients from the TCGA cohort (A) and GEO cohort (B) were divided into three groups (low, mid and high) according to their tumour levels of TGFB1, TGFB2, TGFB3, TGFBR1 or TGFBR2 mRNA.…”
Section: Associations Between the Mrna Levels And The Patients' Clinisupporting
confidence: 89%
“…Thus the association between the expression levels and the patients' clinical outcome may serve as an indicator of the proportion of the three types of tumours. The conflicting results such as that were reported for the associations between the protein levels of TGFβ1 and TβRII and the patients' clinical outcomes [161][162][163][164], were very likely due to that the studied cohorts were composed of different proportions of the three types of tumours.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation